Right of Foreigners to Acquire Real Estate in XIX Century Serbia - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Immigration of rural population from neighboring countries into the Princedom of Serbia started immediately upon the ending of the war period after the Serbian Revolution and had taken place with various intensities in the following decades. Serbian authorities tried to regulate this immigration by adoption of two general legal acts concerning all farmers – foreign citizens who wanted to settle in Serbia. These were Settlement of Foreigners Act introduced on February 27, 1865 and Settlement Act enacted on January 15, 1880. As they were passed under various historical conditions, they differed regarding the aims that had to be reached, but at the same time, as they treated the same subject – settlement, they had certain similarities too. According to both documents, settlers would receive from the Government certain amount of municipal land, assistance in cattle, tools and money, as well as interest-free loans from the local authorities, but only if they apply for Sebian citizenship. Foreigners could not own real property until Serbia gained full independence in 1878. Still, even then, limitations for real property acquisition of foreigners in Serbia were significant. Foreign citizens could obtain immovable property only if their country had signed billateral convention or trade agreement with Serbia that allowed such possibility, and if requirement of reciprocity and Most-Favoured-Nation treatment were fulfilled.